Sound affects: Visualizing music, musicians and (sub)cultural identity in BECK and Scott Pilgrim. Issue 1 (1st July 2015) - Pino, Camilo Diaz
This article discusses the portrayal of popular music in comics as both a product of sensory and emotive experience, and as a determinant of social identity and labour. To this end, it focuses on the Japanese serialized manga BECK and the Canadian graphic novel series Scott Pilgrim. These two works offer comparable perspectives on music and the social mythos of musicianship, as well as sharing similar young male protagonists and social contexts, despite their disparate settings in Tokyo and Toronto, respectively. Through a comparative reading of these texts, this analysis examines contemporary comic book techniques as well as the cross-cultural dynamics of Japanese and Anglo-American comic book cultures, specifically with regard to the portrayal of workers in fields of cultural production. In order to examine their interrelated depictions of music as both sensorial experience and enactment of collective identity, I first draw on the canon of comic book semiotics established by Scott McCloud, Ian Hague, and others to examine the techniques employed by these texts in communicating music as an emotive sensorial experience. In particular I will concentrate on their use of diagrammatic techniques and visual caricature as a means of communicating music – not through attempted synaesthetic effects, but rather through emotive evocation. Second, I look at their representation of musicianship as an area in which the mythology of artistic entrepreneurialism coexists with imperatives of collective identity and lifestyle. I examine the sociologically idiosyncratic manner in which these comics reflect and build upon these mythologies through the filters of class, cultural and generational identity, creating narratives that at times perpetuate – and at others subvert – the grand entrepreneurial narratives ascribed to musicianship within contemporary neo-liberal notions of creative labour.